Constant-time hardware implementation of Modular Inversion with Kaliski’s Algorithm for ECC - Khai Nguyen; Tung Nguyen; Hung Nguyen; Linh Tran (PLoS ONE, 2026)
This paper introduces a hardware architecture designed for constant-time modular inversion over prime fields, a critical function in Elliptic Curve Cryptography (ECC). We use Kaliski’s Almost Inversion Algorithm to develop an efficient FPGA-based solution. The proposed design guarantees constant-time execution, optimizing modular inverse computations for ECC applications. When synthesized on a Xilinx Kintex-7 FPGA, the accelerator reaches a frequency of 222.9 MHz, occupying 1.7k Slices without using any DSP blocks. This work focuses on improving the speed and resource usage of modular inversion units, specifically for resource-constrained digital environments.